Perancangan Interior “Interior World Center” di Surabaya - Renita Olivia Handojo (Intra, 2014)
Interior World Center is a place that contain all needs and matters related to world of interior. The main purpose of Interior World Center is to give access and facilitate people in fulfill their needs that concern and correspond with interior world, that is to say with combine and integrate several interior activity into one in corporated place. Inside of this building there are several commercial space related with the interior world. The commercial spaces will support each other in order to succeed Interior World Center. The commercial spaces are furniture retail and interior accessories, furniture gallery, interior and contractor consultant office, cafe, meeting room, and also room for training and introduction about sustainable design.